FRONT MATTER JEMT VOL 2, NO 2 (2022) - Editor JEMT (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2022)
Containing Cover, Editorial Board, List of Content, Back Cover including the ISSN barcode